Prevalence of bovine mastitis in the Anaime Canyon, a Colombian dairy region, including etiology and antimicrobial resistance - María Sánchez Bonilla, María del Pilar (2018)
The aim of this study was to determine the prevalence of bovine mastitis and the antimicrobial resistance of the pathogens involved in a dairy region of Colombia. Mammary quarters of 348 cows were examined and evaluated using the California Mastitis Test(CMT). CMT-positive samples were cultured for bacteriological isolation and susceptibility to antibiotics by the disk diffusion method. Descriptive statistics and prevalence ratio were calculated. The results indicate that 158 (45.4%) of the cows were positive for CMT. Clinical mastitis was found in seven cows (2.0%) and subclinical mastitis in 151 cows (43.4%). The coagulase-negative staphylococcus (CNS) group was the main pathogen found in 46.7% of the isolates, followed by Staphylococcus aureus (31.1%) and Streptococcus spp (20.7%). Klebsiella pneumoniae and E. coli had a low occurrence (0.5%). CNS, Staphylococcus aureus and Streptococcus spp presented a high degree of resistance to penicillin G and erythromycin, in addition to multiresistance.